Greater and More Focused Measures Are Needed to Tackle Diabetes and Obesity Epidemics in the Nations of the Gulf Cooperation Council - Abdelilah Arredouani (14070786) (2021)
Beyond the suffering of the affected subjects, type 2 diabetes (T2D) and obesity epidemics gripping the Gulf Cooperation Council (GCC) states are expected to seriously jeopardize these nations’ economies and development due to productivity losses. Available data show that healthcare budgets in GCC nations are under tremendous pressure because of diabetes- and obesity-linked comorbidities. Furthermore, T2D, once an over-forties disease, risks becoming a whole-adult-life condition because of obesity-associated early-onset T2D and prediabetes. The incidence of T2D is set to worsen unless efficient actions are taken to fight obesity and prevent the conversion of prediabetes to T2D. There is a consensus that the concomitant increase in obesity rates drives T2D rates upward. Fighting obesity at all levels should, therefore, take center stage for the GCC nations. The battle against obesity and T2D is a long-term and complex one. Therefore, only through concerted efforts between several public and private actors, including health, economic, and urbanization agencies, food producers and retailers, schools, families, youth organizations, sports clubs, and voluntary organizations, can this battle be won. The present review tries to assess the current status of diabetes and obesity epidemics in the GCC context and take stock of some of the policies and initiatives that have been, or need to be, implemented to address their growing burden.  Other information Published in: International Journal of Endocrinology License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1155/2021/6661346